Design-Construction of a Solar Cell Energy Water Pump as a Clean Water Source for People in Sirnajaya Village, Gununghalu District - A. K. Irawan; D. Rusdiana; W. Setiawan; W. Purnama; R. M. Fauzi; S. A. Fauzi; A. H.F. Alfani; M. R. Arfiyogo (Universitas Pendidikan Indonesia (UPI), 2021)
The purpose of this study is to analyse the performance of the solar panels and batteries used to operate the water pump. The results will be used for the application of water pump energy sources in Sirnajaya village, Gununghalu district. The method used to analyse is experimental. The data of the voltage generated by the solar cell and the data of the batteries voltage are collected every hour for six days. Then collect the data of the duration for filling up the water container 500 litres. Results show that the solar panels generate the highest voltage at 12.00 with an average voltage of 19,1 VDC, at 13.00 with an average voltage of 19,1 VDC, and at 14.00 with an average voltage of 18,9 VDC. The result related to the batteries voltage when charging shows the highest voltage at 12.00 with an average voltage of 14,0 VDC, at 13.00 with an average voltage of 14,1 VDC, and 14.00 with an average voltage of 14,1 VDC. The duration for filling up the 500-litre water container takes 60 minutes. These results come because of the various intensity of the sun and the position of the sun against the solar panels which give an impact to the voltage value from the solar panels and the batteries. This study gives impacts on the application of solar panels for various uses.